Environmentally oriented energy policy and stock returns: an empirical analysis - Ulrich Oberndorfer; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper analyzes the effect of environmental regulation on stock returns (as a measure of economic performance) for German energy corporations. By using event study methodology, we consider the last minute victory of the acting government in the 2002 German federal elections to the Lower House of Parliament (Bundestag). The government coalition consisted of Social Democrats and the Green party and was generally associated with a paradigm shift in environmental and particularly energy policy towards the promotion of renewable energies and a phasing out of nuclear energy. In contrast, the opposing Christian Democrats and Liberal party signaled different priorities in line with traditional energy policy. Compared with other environmental event studies, we include insights from modern empirical finance and therefore also apply the Fama-French three-factor model to estimate the abnormal daily and monthly stock returns. The main estimation results of the empirical analysis imply (1) no evidence of a general negative impact of the 2002 Bundestag elections on stock returns for traditional utilities and (2) a positive albeit transitory short-run effect for the entire group of renewable energy corporations. We conclude that the 2002 Bundestag elections and therefore stringent environmental regulation had at least no general negative effect on the economic performance of energy corporations. One reason for this could be that the compliance costs of the government?s environmentally oriented energy policy were lower for traditional utilities than expected.
Keywords: Q42; G14; Q48; G12; 330; Environmental regulation; Energy policy; Nuclear energy; Renewable energies; Event study; CAPM; Market model; Three-factor model